Old Parliament Hall, Edinburgh: Statues of Justice and Mercy - Ross, Thomas (Proceedings of the Society of Antiquaries of Scotland, 1919)
These statues, with the accompanying carved stones, were found in August 1909 in the back garden of No. 37 Drummond Place. The two figures, with the stone containing the city arms, have been placed within the Old Parliament Hall; while the pediment stone with the open-arched crown surmounted by a cross, and having the date 1636, has been placed over a doorway in the new piazza. The statues had been removed from the Old Parliament Hall in 1824. They are thought to have been sculptured by Alexander Mylne, who was born in Perth in 1613.